Gamifying news for the miOne online community - Regalado, Francisco Silva Ferreira (2021)
The growing ageing population, combined with the increasing use of information and communication technologies, i.e. online communities, by older adults, has heightened the need to study the challenges and solutions in presenting empathic products that meet the users’ needs, customized to their context. Online news present growing challenges due to new interaction paradigms and games have already demonstrated to be very effective in capturing user’s attention, as well as the adoption of game elements and techniques to non-game contexts - i.e. gamification. This Development Research reports, firstly, the motivations and the context of use in digital platforms by adult learners from the Universities of the Third Age (UTAs), supporting the design and development of a gamification strategy in the context of an online community entitled miOne. To meet this challenge, a literature review centered on the keywords 'Older Adults', 'Gamification', 'Motivation and Engagement' and 'Digital Media' was performed, as well as a questionnaire survey that was administered to 248 people aged 50 and over from 16 different countries. Secondly, a digital artifact was developed, applying gamification to online news, within the miOne online community. This artifact was validated with 6 national newspaper players to understand the challenges posed to the journalistic sector and assess the product’s relevancy to the market. Finally, the proposed solution was tested with 11 participants from Universities of the Third Age. The results suggest that the developed mechanics and gamification elements can engage older adults with online news on digital platforms. Additionally, these can guide the integration of a gamification strategy in the previously mentioned context. These interconnected elements are: (i) a leaderboard with the most weekly news’ interactions; (ii) levels with different missions and rewards (external and internal to the platform); and (iii) a community-endorsed award system to recognize and validate user-generated content towards news.